Toward a New Quasi-Parliamentary and Quasi-Federal Political System in Costa Rica: Size Versus Effectiveness of the Democratic System - Meoño-Segura, Johnny (2011)
The author provides a diagnostic analysis of the strategic state of decentralization in Costa Rica from a perspective that goes beyond the municipal level, and proposes a new political system that requires constitutional and legal changes and aims to serve as a framework to help current and future generations of analysts and political leaders overcome the recurring weaknesses that have characterized assessments and proposals regarding municipal affairs and, to a greater extent, decentralization. This is an unprecedented approach in the country, particularly because it challenges at its roots the colonial-era political culture that the author has demonstrated still dominates the visions and practices of government and administration in Latin America, and especially in Costa Rica. His proposals for a quasi-parliamentary and quasi-federal system, presidential reelection, parliamentary careers, and the recall of elected officials via popular referendums constitute a comprehensive proposal for viable political change.